Towards a new culture of computer games – from computerisation to smartphonisation - du Vall, Marta; Majorek, Marta (Replay. The Polish Journal of Game Studies, 2014)
In this paper the authors focus on the crucial change of thinking about what computer really is, and then attempt to determine the essential elements of new games designed specifically for mobile computers. The authors characterize this type of entertainment, which enables them to outline potential scenarios for the development of this technological sphere and its impact on contemporary cultural life.